2018
DOI: 10.1182/blood-2018-03-834598
|View full text |Cite
|
Sign up to set email alerts
|

Polyreactive IgM initiates complement activation by PF4/heparin complexes through the classical pathway

Abstract: Abstract The mechanisms by which exposure to heparin initiates antibody responses in many, if not most, recipients are poorly understood. We recently demonstrated that antigenic platelet factor 4 (PF4)/heparin complexes activate complement in plasma and bind to B cells. Here, we describe how this process is initiated. We observed wide stable variation in complement activation when PF4/heparin was added to plasma of healthy donors, indicating a responder “phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 52 publications
5
33
0
3
Order By: Relevance
“…S1H). This allowed us to claim, in agreement with previously published data (23), that heparin weakly pre-activates granulocytes in our experimental setting. Thus, hirudin-treated blood samples were used in all further experiments.…”
Section: Granulocytes Behavior Change In the Process Of Crawling Amonsupporting
confidence: 92%
“…S1H). This allowed us to claim, in agreement with previously published data (23), that heparin weakly pre-activates granulocytes in our experimental setting. Thus, hirudin-treated blood samples were used in all further experiments.…”
Section: Granulocytes Behavior Change In the Process Of Crawling Amonsupporting
confidence: 92%
“…Even in the absence of underlying genetic causes, dysregulation of complement can cause inappropriate activation leading to adverse effects, as is the case in ischemia/reperfusion injury or transplant rejection [ 8 ]. In other diseases, including neurological disorders like Alzheimer’s disease [ 12 , 13 , 14 ] or thrombotic conditions like heparin-induced thrombocytopenia (HIT) [ 15 , 16 ], the underlying mechanisms of complement involvement are only now becoming more clear. Nevertheless, mounting evidence for the involvement of complement in many human diseases has spurred a resurgence of activity in the field of complement-directed therapeutics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More rarely, IgM can be present at high concentration in patients with HIT, without IgGs. The mechanisms involved are not totally understood, but recently it was demonstrated that anti-HPF4 IgM antibodies can activate complement and induce platelet destruction [39]. Altogether, the different activities described here above help to understand why HPF4 antibodies, including IgG isotypes, can remain asymptomatic in many patients and produce (especially IgG isotypes with high HPF4 affinity) HIT or HITT only in a few of them.…”
Section: Pathogenicity and Mode Of Action Of Heparin-dependent Antibomentioning
confidence: 87%
“…The three isotypes (IgG, IgA, or IgM) can be present [13,19], but IgGs are formed very rapidly, which is unusual in the early stage of the immune response, and IgGs can become rapidly pathogenic [19]. In rare cases, only IgA (especially in patients with cancer) or IgM isotypes are identified [39]. Following heparin treatment cessation, antibodies disappear from blood circulation within about 3 months.…”
Section: Heparin-dependent Antibodies In Clinical Settingsmentioning
confidence: 99%